Retraction Note: The Role of Nanomaterials in Advancing Sustainable Healthcare Practices - Kumar Sandeep; Yadav Rajat; Kumar Rahul; Raturi Anuj; Rao A.L.N; Kumar Anil; Shirish Boob Nandini (E3S Web of Conferences)
This paper has been formally retracted from publication by the Publisher due to the fact that it has no scientific validity Request approved by the Publisher on October 15, 2024.